OPPORTUNITIES FOR INCREASING THE EFFICIENCY OF GROWING AND USING MEDICINAL PLANTS - Mukhammadieva Dilafruz Alisher kizi (European Science Publishing, 2025)
The article has developed proposals with an analysis of the importance of the development of the system of cultivation and sale of medicinal plants in Uzbekistan, the reforms carried out in recent years, the directions of scientists conducting research in this regard, and the dynamics of development.
Keywords: Medicinal plants, pandemics, forest lands, investment projects, research, land area, growth rates, biodiversity.